Optimum values of Second Gruneisen parameter (q) for Iron, Vanadium and Titanium - Dr. Adnan M. Al-Sheihk; Janan F. Ahmad; Dr. Mumtaz M. Saleh (مجلة التربية والعلم, 2006)
In the present work a numerical model is constructed for the joint optimization of experimental data on recoilless fraction, using an improved relation between Debye temperature and the volume dependence of Griineisen parameter y, and the second GrUneisen parameter q. This model shows the optimum q values for Iron, Vanadium and Titanium.